Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.juro.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Eraser Laser Enucleation of the Prostate: Preliminary Report

Abstract: Eraser laser prostate enucleation and bipolar transurethral prostate resection were equally safe and effective to relieve bladder outflow obstruction and lower urinary tract symptoms. This laser technique has the advantage of less blood loss, and shorter catheter time and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Also fluid absorption betides in the bipolar TURP and volume overload may be problematic in patients with severe cardio-pulmonic disorders (23,27,31,36). In the last decade, laser energy has been applied with high safety and efficacy for vaporization or enucleation of hypertrophic large volume prostate (6,9,(11)(12)(13)(40)(41)(42). But laser therapy may be accompanied with the use of multiple techniques and different wattage, technical complexity, prolonged operative time, higher applied energy and re-operation rate in the larger prostate volume cases, high cost equipment and inaccessibility in many centers (6,9,(11)(12)(13)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also fluid absorption betides in the bipolar TURP and volume overload may be problematic in patients with severe cardio-pulmonic disorders (23,27,31,36). In the last decade, laser energy has been applied with high safety and efficacy for vaporization or enucleation of hypertrophic large volume prostate (6,9,(11)(12)(13)(40)(41)(42). But laser therapy may be accompanied with the use of multiple techniques and different wattage, technical complexity, prolonged operative time, higher applied energy and re-operation rate in the larger prostate volume cases, high cost equipment and inaccessibility in many centers (6,9,(11)(12)(13)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, laser energy has been applied with high safety and efficacy for vaporization or enucleation of hypertrophic large volume prostate (6,9,(11)(12)(13)(40)(41)(42). But laser therapy may be accompanied with the use of multiple techniques and different wattage, technical complexity, prolonged operative time, higher applied energy and re-operation rate in the larger prostate volume cases, high cost equipment and inaccessibility in many centers (6,9,(11)(12)(13)(40)(41)(42). Beside morbidity and complication, attention to other outcomes, prostate volume, anesthesia risk, patient satisfaction, cost-benefit or cost--effectiveness, learning curve, easy accessing and performing is important in the selection of preferable procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various lasers have been introduced as alternatives to TURP, including Nd:YAG, Ho:YAG, KTP:YAG and Tm-laser. Diode lasers have also been used for BPE treatment and recent studies have reported results comparable to TURP [2,3]. The radiation emitted by a diode has different properties based on the different wavelengths used, resulting in completely different cutting and penetration of the tissue and vessel sealing.…”
Section: Introductionmentioning
confidence: 99%
“…Our first clinical experience revealed very good cutting properties and coagulation efficiency for this particular wavelength [2]. To understand the mode of action better, we decided to investigate the effect of the Eraser diode laser on human prostate tissue.…”
Section: Introductionmentioning
confidence: 99%